Performance anxiety in media culture the trauma of appearance and the drama of disappearance - Bailey, Steven (Palgrave Macmillan, 2016)
"Performance Anxiety in Media Culture explores the culture of performance anxiety in the media-saturated contemporary world. It uses comparative case studies including film, social media, and popular music to examine the ways that personal concern regarding self-presentation becomes transformed into shared cultural expressions through the use of media technologies. Three initial chapters are dedicated to exploring the work of Erving Goffman, Jacques Lacan, and Jean Baudrillard as critical for a thorough understanding of how implications of a range of recent transformations in the methods for staging social performances are staged and in the ways that they are experienced and interpreted by others. Three subsequent chapters explore diverse case studies in the culture of performance anxiety: the representation of such anxieties in recent French cinema, the appearance of them in the world of fashion-based 'outfit of the day' blogs, and the attempt to refine a more fixed social persona in the nostalgic culture of rockabilly music"--